The wrong hands - Billingham, Mark (Billingham, Mark. Detective Miller novel ;, 2024)
"Unconventional Detective Declan Miller has a problem. Still desperate to solve the murder of his wife, a young man has just appeared on his doorstep with a briefcase . . . containing a pair of severed hands. Miller knows this case is proof of a contract killing commissioned by local ne'er-do-well Wayne Cutler-a man he suspects might also be responsible for his wife's death. Now Miller has leverage, but unfortunately, he also has something that both Cutler and a villainous fast-food kingpin are desperate to get hold of. Chuck in a Midsomer Murders-obsessed hitman, a psychotic welder, and a woman driven over the edge by a wayward Crème Egg, and Miller is in a mess that even he might not be able to dance his way out of"--